Sensitivity analysis for the determination of characteristic curves of dead time vs transfer power applied to transmission lines - Morales Garcia, John Armando (2020)
For the transmission of large electric power blocks to large lengths, Extra High Voltage systems are a good alternative, where the elements that make up the transmission system must be designed in such a way that they offer high reliability and availability during their operation. In this context, it is necessary to perform a proper single-phase autoreclosure, determining the power transmission capacity and the reclosure dead time in the event of single-phase line to-ground failure considering a single-phase opening and reclosing scheme and Transient Stability of the system. In this sense, this research proposes a methodology to determine characteristic curves corresponding to dead time vs active power of transfer that guarantee a maximum transfer of active power through the transmission lines, and transient stability due to failure, opening and single-phase reclosing events. These characteristic curves will make it possible to decide, from the point of view of transient stability, the most suitable value for adjusting the single-phase reclosing dead time and the dispatched power of the generation central.